Employee Behavior and Job Satisfaction in an Organization Using Herzberg's Two-Factor Model: A Theoretical Study - Joseph, Amal (Jurnal Multidisiplin Madani, 2023)
A person's behaviour encompasses not just how they handle themselves in social situations but also how they express strong emotions like joy, anger, love, and sadness while at work. Organizations consist of groups of people who share a common purpose and work together to realise it. If a business wants to succeed in its mission, it requires the full cooperation and coordination of all its personnel. The efficiency and success of a company hinge on the efforts and outlook of its employees. Changes in behaviour have effects on the group. Psychologist Fredrick Irving Herzberg, or "Fred," of the United States, developed the Motivation Hygiene Theory of Job Satisfaction. His idea is an attempt to explain what motivates people to work together toward a common objective in an organisation. The goal is to ensure the organization's success. The mood at work can be affected in both positive and negative ways by employees' levels of satisfaction with their jobs. This article demonstrates how workplace cleanliness concerns including company regulations, oversight, position, and job security can contribute to employee motivation and satisfaction. This research examines how employees' attitudes and happiness with their work change inside an organisation that practises the Herzberg two-factor theory